Great Wolf and the Good Woodsman - Hoover, Helen (Fesler-Lampert Minnesota heritage book series., 2005)
The miracle of Christmas permits the animals to work together as friends, despite their fear of the Great Wolf, and to rescue their beloved woodsman.